2011
DOI: 10.5121/ijmit.2011.3301
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Technology Acceptance Model in Explaining Effect on E-Commerce Application System

Abstract: Today e-commerce has become crucial element to transform some of the world countries into an information society. Business to consumer (B2C) in the developing countries is not yet a normalcy as compared to the developed countries. Consumer behaviour research has shown disappointing results regarding the overall use of the Web for online shopping, despite its considerable promise as a channel for commerce. As the use of the Internet continues to grow in all aspects of daily life, there is an increasing need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 6 publications
3
31
1
Order By: Relevance
“…Preference to electronic payment systems is further driven by previous use of the system which translates itself in the ease of use and usefulness. On the contrary, Johar and Awalluddin (2011) found that the age groups 51-60 years had higher tendency to adopt e-commerce. According to Nwaolisa and Kasie (2012) those who had previous experience were likely to prefer more than one electronic payment system signifying control over the systems and perceived convenience.…”
Section: Socio-demographic and Economic Characteristics Of Respondentsmentioning
confidence: 84%
See 2 more Smart Citations
“…Preference to electronic payment systems is further driven by previous use of the system which translates itself in the ease of use and usefulness. On the contrary, Johar and Awalluddin (2011) found that the age groups 51-60 years had higher tendency to adopt e-commerce. According to Nwaolisa and Kasie (2012) those who had previous experience were likely to prefer more than one electronic payment system signifying control over the systems and perceived convenience.…”
Section: Socio-demographic and Economic Characteristics Of Respondentsmentioning
confidence: 84%
“…Access to and utilization of banking services could explain the lower preference to electronic payment systems in favour of cash (Scholz & Seshedri, 2009;Mann & Mann, 2011). This could be the result of savings due to higher earnings (Johar & Awalluddin, 2011;Lee, Lole, & Tan, 2013), greater decision-making power at household level (men have more decision power in our patriarchal societies). This could explain why some clients are less likely to prefer to use electronic payment systems.…”
Section: Socio-demographic and Economic Characteristics Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(As suggested in [8], in developing e-commerce system consumers' behavior must be studied and resolved carefully. This research has contributed in resolving some part of ecommerce system, specifically the mobile marketing sub-system.…”
Section: Resultsmentioning
confidence: 99%
“…TAM is considered most relevant in predicting the desire as well as the readiness to adopt the technology [11]. The study of [6] describes TAM undergoing modification and development.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%